Implementasi VPN Menggunakan Protokol L2TP Untuk Pengelolaan NAS (Network Attached Storage) Pada STB - Dimas Zaldiyanto; Subektiningsih; Irma Rofni Wulandari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Implementing Virtual Private Network (VPN) in remote Network Attached Storage (NAS) control using L2TP protocol on Mikrotik Router. This study uses a used device, Set Top Box HG680P, converted into a NAS server as a more economical and environmentally friendly alternative to buying a conventional NAS server. Implementation of L2TP VPN via Mikrotik facilitates remote access with guaranteed security levels. Testing was carried out using two devices, a Laptop and a Smartphone, which were used to access and transfer data via a VPN network. The test results showed that the VPN implementation successfully facilitated access from various locations and data transfer with good performance. In testing, the download speed was 50 Mbps, and the upload speed was 10 Mbps for file sizes from 50 Mb to 1000 Mb. The test results using VPN gave an average speed of all file transfers of 15.12Mb/s with an average transfer time of 4 minutes 14 seconds. Testing was also carried out by disconnecting the VPN connection on Mikrotik. The unconnected VPN on Mikrotik causes the browser to fail to access the site because the VPN cannot access information on the NAS Server. Therefore, VPNs play an important role as a bridge to access the NAS server outside the local network. In access management, restrictions are imposed on each user to increase security when accessing or sharing files on the NAS server with others. The goal is for users to have access restrictions, only being able to access the specified parts. This research is expected to contribute to developing secure, economical, and efficient network solutions, especially in utilizing used devices for data management.